Perceived ethnic discrimination and school connectedness among adolescents in Finland: Role of family background and sex - Isik Zeliha Ulubas; Kaj Björkqvist; Patrik Söderberg (Universitas Ahmad Dahlan, 2021)
The study investigates the effect of immigrant background and sex on perceived ethnic discrimination and school connectedness in Finland. An online questionnaire was completed by 1,827 adolescents (12-19 years of age) from both Finnish and Swedish speaking schools in Western Finland. Adolescents’ family background was categorized as either native, multicultural, or immigrant. Perceived ethnic discrimination was examined according to its source, whether it acted out by peers, by teachers, or by someone else. Adolescents with an immigrant background were found to have higher scores of perceived ethnic discrimination regardless of its source, and lower school connectedness than other groups. Boys had higher scores of perceived ethnic discrimination by peers and by someone else, and they also reported higher school connectedness than girls. There was also a significant interaction effect between immigrant background and student sex, so that girls with a multicultural background experienced higher levels of discrimination by peers and discrimination by someone else than boys with a multicultural background.